2012
DOI: 10.1002/ijc.27802
|View full text |Cite
|
Sign up to set email alerts
|

Proportion cured models applied to 23 cancer sites in Norway

Abstract: Statistical cure is reached when a group of patients has the same mortality as cancer-free individuals. Cure models predict the cured proportion and the median survival of fatal cases. Cure models have seldom been applied and tested systematically across all major cancer sites. Incidence and follow-up data on 23 cancer sites recorded at the Cancer Registry of Norway 1963-2007 were obtained. Mixture cure models were fitted to obtain trends and up-to-date estimates (based on period approach) assuming cured and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 33 publications
3
37
1
Order By: Relevance
“…It was much higher than results in our study, which may be due to earlier stage at diagnosis and improvement in treatment caused by the gastric cancer management . The cure proportions reported in Europe countries were approximately 20%‐30%, which were lower than those in Japan and recent period in our study . The difference in cure proportion usually related to the gastric cancer treatment and stage at diagnosis .…”
Section: Discussioncontrasting
confidence: 85%
“…It was much higher than results in our study, which may be due to earlier stage at diagnosis and improvement in treatment caused by the gastric cancer management . The cure proportions reported in Europe countries were approximately 20%‐30%, which were lower than those in Japan and recent period in our study . The difference in cure proportion usually related to the gastric cancer treatment and stage at diagnosis .…”
Section: Discussioncontrasting
confidence: 85%
“…In a recent study by Cvancarova et al, cure models were applied to major cancer sites recorded in the Cancer Registry of Norway between 1963 and 2007, including a wide array of cancers including those of the esophagus, stomach, pancreas, liver, colon, bladder, and central nervous system, among others . In this study, although cancers of bladder and central nervous system had the highest percentage of cured patients (67.4% and 64.0%, respectively), those of the pancreas and liver had among the lowest rates (5.7% and 9.9%, respectively) . A separate study conducted among 818,902 Italian patients with cancer confirmed a low cure rate for patients with liver and pancreatic cancers (<10%) .…”
Section: Introductionmentioning
confidence: 75%
“…In doing this, the nonmixture cure model can provide a clinically useful measure of the probability of cure among patients with cancer after treatment . In a recent study by Cvancarova et al, cure models were applied to major cancer sites recorded in the Cancer Registry of Norway between 1963 and 2007, including a wide array of cancers including those of the esophagus, stomach, pancreas, liver, colon, bladder, and central nervous system, among others . In this study, although cancers of bladder and central nervous system had the highest percentage of cured patients (67.4% and 64.0%, respectively), those of the pancreas and liver had among the lowest rates (5.7% and 9.9%, respectively) .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Cure models have been introduced in the statistical literature and more recently have been applied in the clinical literature. One recent study investigated the probability to be cured and the time to cure among patients following surgery for a wide variety of tumors, including mouth and pharynx, esophagus, lung and trachea, ovary, bladder, non-Hodgkin lymphoma and leukemia [20]. In a separate study, investigators evaluated the cure fraction of patients with liver and pancreatic cancers [21].…”
Section: Introductionmentioning
confidence: 99%